2013
DOI: 10.1038/ajg.2013.204
|View full text |Cite
|
Sign up to set email alerts
|

The 22/11 Risk Prediction Model: A Validated Model for Predicting 30-Day Mortality in Patients With Cirrhosis and Spontaneous Bacterial Peritonitis

Abstract: In cirrhotic patients with SBP receiving standard therapy, MELD score ≥22 and peripheral blood leukocyte count ≥11×10⁹ cells/l are validated independent predictors of mortality. The mortality in a patient without either poor prognostic variable is ≤10% and with both variables is ≥50%. Trials aiming to reduce mortality should target patients in the moderate-risk to high-risk groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
34
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 30 publications
7
34
1
Order By: Relevance
“…We stratified the patients with SBP in those above and below the median of calprotectin and the ratio to total protein and found significantly different survival when analyzing these two groups in a Kaplan-Meier plot [p = 0.042 for calprotectin and the ratio ( Figure 5B), respectively]. In univariate analysis, presence of HCC (p = 0.008) and, similar to a previous report [18], a MELD score > 21 (p = 0.003) were additionally associated with poor 30-day survival. A multivariate Cox regression analysis on survival revealed that a MELD score > 21 (p = 0.012) and a ratio of calprotein to total protein above the median (p = 0.039), remained independent predictors of poor 30-day survival.…”
Section: Calprotectin Levels and The Ratio To Total Protein Correlatesupporting
confidence: 72%
See 1 more Smart Citation
“…We stratified the patients with SBP in those above and below the median of calprotectin and the ratio to total protein and found significantly different survival when analyzing these two groups in a Kaplan-Meier plot [p = 0.042 for calprotectin and the ratio ( Figure 5B), respectively]. In univariate analysis, presence of HCC (p = 0.008) and, similar to a previous report [18], a MELD score > 21 (p = 0.003) were additionally associated with poor 30-day survival. A multivariate Cox regression analysis on survival revealed that a MELD score > 21 (p = 0.012) and a ratio of calprotein to total protein above the median (p = 0.039), remained independent predictors of poor 30-day survival.…”
Section: Calprotectin Levels and The Ratio To Total Protein Correlatesupporting
confidence: 72%
“…An excessive inflammatory reaction may be detrimental in the context of liver cirrhosis, a finding that is also suggested in a rat model of SBP [40]. For daily practice, different clinical and blood parameters, including the MELD score, blood leukocyte count and creatinine, but no direct markers of peritoneal infection have been proposed to define the mortality risk for patients with SBP [1,18]. In contrast to ascites cell counts, ascites calprotectin or the ratio to total protein may provide not only diagnostic, but also prognostic information by reflecting the severity of the local peritoneal inflammation.…”
Section: Discussionmentioning
confidence: 97%
“…16 In a study of 184 patients, 30-day mortality rate was 27% in patients with a Model for End-Stage Liver Disease score of 20. 2 Our study also included patients in poor condition with correspondingly high Model for End-Stage Liver Disease scores. 2 A limitation of our study was the inability to include patients who met the inclusion criteria but had medical records that were inaccessible or had chronic renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…2 Our study also included patients in poor condition with correspondingly high Model for End-Stage Liver Disease scores. 2 A limitation of our study was the inability to include patients who met the inclusion criteria but had medical records that were inaccessible or had chronic renal failure. In conclusion, most of our patients were at advanced stage of cirrhosis, with treatment efficiency below our expectations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation